Public health activism: success story of overcoming barriers to health care faced by a migrant family - Bhattacharya, Sudip; Trusty, Khumukcham; Aggarwal, Arun Kumar (International Journal Of Community Medicine And Public Health, 2017)
This is a case study from a village in Haryana. A migrant family from another state was working in poultry farm. Family had six children. Youngest was girl infant with grade IV malnutrition and unimmunised. This family was denied immunisation, registration to Anganwari centre, and there were issues of child labour. With public health activism, all these problems were solved. This case study demonstrates that if there is strong commitment and confidence among public health practitioners, they can overcome most of the barriers. Such Public Health Activism should be promoted.